Advances in Maritime Safety - Young-Soo Park; Jung-Sik Jeong; Yusuf Volkan Aydogdu (Journal of Marine Science and Engineering, 2022)
Due to the nature of business, maritime safety plays a paramount role in preventing damage to property and danger to life in the maritime industry [...]